Thermo-Mechanical Modelling of Friction Stir Processing of AZ91 Alloy: Using Smoothed-Particle Hydrodynamics - Roshan Vijay Marode; Srinivasa Rao Pedapati; Tamiru Alemu Lemma; Venkata Somi Reddy Janga (Lubricants, 2022)
A thermo-mechanical model of friction stir processing (FSP) using the Altair based on meshless Smoothed-Particle Hydrodynamics (SPH) was developed and verified experimentally. Process parameters adopted for both experimentation and simulation during the FSP of AZ91 were 1000 rpm tool stirring speed, 40 mm/min tool advancing speed, and 0° tool tilt angle. The numerical analysis predicted the temperature distribution and material movement in the three phases: plunging, dwelling, and traversing. Simulated temperatures during the traversal phase were found to be greater than experimental temperatures using the Ti32 thermal camera as the heat was only transported by friction and plastic deformation. Peak temperatures for all three phases were observed to be in the range of 47% to 87% of the material’s melting point and are in accordance with the findings of the experiments. The SPH mesh-free model was proven to be capable of predicting the in-process thermal-mechanical state variables during and after the process by extracting morphology. The material movement around the tool has been predicted using SPH node tracking, which further anticipates that there was no complete flow of SPH nodes from RS to AS, leaving a gap that must be filled. Post-processed morphology shows inadequacy in the material flow due to lower compressive force. It formed the wormhole at the advancing side’s trailing and was verified experimentally.